P186 Chest Drain Care Bundle improves Chest Drain Insertion in District General Hospital. (12th November 2015) - Steer, H; Hutton, J; Graham, S; Jones, R
Abstract : Introduction and objectives: Chest drain insertion is a common advanced procedure with a significant associated risk of pain, distress and serious complications. Nationally, audit and patient safety work has highlighted a number of safety concerns around chest drain insertion. Previous audit work has demonstrated poor levels of documentation; particularly around use of pre-medication, use of ultrasound guidance and consent. This has obvious potential consequences for patient safety and thus is an important target for improvement work. Method: National best practice standards were identified through review of national guidance. This work quantifies current standards of documentation in Gloucestershire against national best practice standards. Drain insertion was prospectively analysed over a 3 month period to establish baseline standards of documentation. A combination of accessible and easy-to-read guidelines, education and the introduction of a chest drain bundle were introduced. Chest drain insertion was then re-audited over a further 3 month period and assessed for improvement. Results: The data set included 24 pre-intervention and 23 post-intervention. Results demonstrated an improvement in many areas of documentation. Prior to the intervention, documentation was found to be poor; especially in areas related to consent, use of ultrasonography, pre-medication, post-procedure advice, details regarding length and size of drain and investigations requested. Overall the results showed improvement in most areas of documentation. The care bundle demonstrated improvement in documentation compared to the classical "freehand" documentation. However, only 40% of cases used the new proforma due to a mixture of staff rotation and an unexpectedly high proportion of drains inserted in non-targeted areas including the emergency department, theatre and intensive care. Outcomes were also compared against the recent national findings from the 2015 British Thoracic Society Pleural Procedures audit. Use of the chest drain bundle created improved compliance with several key standards; particularly written consent, bedside ultrasonography, nursing chest drain observation and care on designated respiratory ward. Conclusion: The chest drain care bundle improves documentation of this important procedure. This is important to ensure uniformity in clinical "best" practice, aid communication and protect patients. Further improvements can be made by more widespread education and access to the care bundle.